2011
DOI: 10.1089/bfm.2010.0061
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-Based Education Program Improves Breastfeeding Knowledge of Maternal–Child Healthcare Providers

Abstract: Use of an Internet-based educational program improved knowledge of MCH providers as measured by pretest and posttest scores. Knowledge of the growth of breastfed infants is particularly poor. Increasing knowledge is the first step in improving clinical practice that is necessary for increasing breastfeeding rates and duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 31 publications
0
42
0
Order By: Relevance
“…A total of 857 students were interviewed. The mean age of the participants (493 female/364 male) was 21.1 ± 2.0 years (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The fifty percent (427) of the participants was student in School of Medicine, 37% (319) of them was student in Nursing Department of Faculty of Health Sciences and 13% (111) of them was student in Midwifery Department of Faculty of Health Sciences.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 857 students were interviewed. The mean age of the participants (493 female/364 male) was 21.1 ± 2.0 years (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). The fifty percent (427) of the participants was student in School of Medicine, 37% (319) of them was student in Nursing Department of Faculty of Health Sciences and 13% (111) of them was student in Midwifery Department of Faculty of Health Sciences.…”
Section: Resultsmentioning
confidence: 99%
“…This diabetes prevention site shows promise for promoting behavior change. Other eHealth interventions have also shown support for behavior change ranging from the promotion of physical activity and/or proper nutrition among a workforce [30,31], to information about influenza and the common cold [28], to breastfeeding education [32], to education about mammography aimed at Taiwanese women [33], to patients suffering from depression [34] and schizophrenia [27]. …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in the use of the Internet to provide information, reassurance, encouragement, and reinforcement of breastfeeding among expectant and new mothers (Dornan & Oermann, 2006;Riordan, 2000;Thomas & Shaikh, 2007), although there is wide variability in the accuracy, credibility and extent of information about breastfeeding online (Shaikh & Scott, 2005). Previous studies have found that breastfeeding promotion programs delivered via the Internet significantly improved knowledge, positive beliefs, and breastfeeding intentions than offline, healthcare provider-based interventions (O'Connor, Brown, & Lewin, 2011;Pate, 2009). Despite the increasing interest in Internet-based breastfeeding promotion, education, and programs, the most recent literature review on strategies to support breastfeeding (see : Demirtas, 2012) heavily focuses on face-to-face communication between mothers and family members or health professionals.…”
Section: Theoretical Frameworkmentioning
confidence: 99%